Action Initiation Shapes Mesolimbic Dopamine Encoding of Future Rewards - Syed, Emilie C.J. (Nat Neurosci, 2015)
It is widely held that dopamine signaling encodes predictions of future rewards and such predictions are regularly used to drive behavior, but the relationship between these two is poorly defined. Here, we demonstrate in rats that nucleus accumbens dopamine following a reward-predicting cue is attenuated unless movement is correctly initiated. These results demonstrate that dopamine release in this region is contingent upon correct action initiation and not just reward prediction.